The East Siberian Sea as a transition zone between pacific-derived waters and Arctic shelf waters; Geophysical Research Letters; Vol. 32, iss. 10 - Semiletov I. P. Igor Petrovich; Dudarev O. V. Oleg Viktorovich; Luchin V.; Charkin A. N. Aleksandr Nikolaevich; Shin Kyung-Hoon; Tanaka Nori (2005, 2005)
Title screen